New palm oil products by enzymatic interesterification and dry fractionation / Saw Mei Huey - Saw, Mei Huey (2010)
Palm olein is one of the major palm oil products that domestically and industrially used as cooking or frying oil. Palm olein tends to crystallize at low temperature that limits its usage in temperate countries. In spite of various nutritional studies, palm olein is also not well considered as recommended choice due to its higher saturation content. Against these factors, there is a need to reduce its saturation content. In this study, the saturation content in palm olein was reduced through the combination of enzymatic interesterification and dry fractionation. Enzymatic interesterification allows interchanging of acyl groups between and within triacylglycerols (TAG) molecules, specifically at sn-1 and -3 positions to form new TAG species such as triunsaturated (mainly OLL, OLO, and OOO) and trisaturated TAG (PPP and PPS). The high melting trisaturated TAG can facilitate the crystallization of the interesterified palm olein, and easily removed as stearin fraction during fractionation process. Two sn-1,3 specific immobilized lipases; Lipozyme® TL IM (Thermomyces Lanuginosa) and Lipozyme® RM IM (Rhizomucor Miehei) were selected as biocatalysts for interesterification in solvent-free system. The pilot-scale enzymatic interesterification using packed-bed Lipozyme® TL IM produced the greatest amount of trisaturated TAG (5.5%), followed by 5%w/w of Lipozyme® TL IM in batch reaction (4.5%) and 2%w/w of Lipozyme® RM IM in batch reaction (1.9%). The enzymatic interesterification with combination of dry fractionation had successfully reduced the saturation content of palm olein IV 62 from 41.7% to 33.3%, and 33.9%, 36.5% through packed-bed TLIM, batch TLIM, and batch RMIM, respectively. The IV was increased from 62.0 to 70.7 for batch TLIM and packed-bed TLIM olein products, and 67.4 for batch RMIM olein product.